Litanic prayer - poetic litany: French paraphrases till the nineteenth century - Kowalska, Magdalena (Romanica Olomucensia, 2017)
The paper analyses five examples of French litanic paraphrases from different periods: the medieval paraphrase La letanie from the Book of Hours of the Diocese of Evreux and the farce Le pelerinage de marriage, Paraphrase des Litanies de la Vierge Marie of Martial de Brives (1653), Litanies de la Sainte Vierge, ou de Lorette. Traduites en vers francais, et paraphrasees en forme d'ode sacree (1837) of Marie-Louis-Auguste Demartin du Tyrac Marcellus and Les Litanies de Satan of Charles Baudelaire. The paper aims to explore the most common methods used to transfigure the liturgical form into a literary work, amongst others: enclosing litanic lines into stanzaic form, maintaining the Latin intercalations, parodying them, and applying a monorhytmic strategy. The analysis involves raising the themes of the identity of the person speaking in the paraphrases (singular or plural) and of the shape and order of two fundamental elements of litanic texts, that is, invocations and supplications.
Keywords: litany; paraphrase; prayer; Latin intercalations; invocation; supplication